Methodology of hazards identification in construction work course - Hoła, Bożena (Journal of Civil Engineering and Management, 2010)
The building industry is characterised by high variety and variability of working processes and work environment conditions, which is conductive to accidents at work. It is pointed out that the process of analyzing hazards in construction work should correspond to the successive changes in the state of the civil structure being erected and to the associated changes in the state of the production system. The starting‐point for identifying hazards and determining the place and time of their occurrence should be a correctly drawn up graphic schedule of construction work.